2018
DOI: 10.1002/ps.4850
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structure–activity relationship (QSAR) analysis of plant‐derived compounds with larvicidal activity against Zika Aedes aegypti (Diptera: Culicidae) vector using freely available descriptors

Abstract: The QSAR model surpasses previously published models based on geometrical descriptors, thereby representing a suitable tool for predicting larvicidal activity against the vector A. aegypti using a conformation-independent approach. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Elucidation of mode of action of EOs is important for insect control because it may give useful information on the most appropriate formulation, delivery means and resistance management (Sim et al, ). Future studies emphasizing on determining the mechanism of action, rational design, structure–activity studies, formulation and field trials of the terpenes and EOs as presently going on (Alencar Filho et al, ; Saavedra et al, ; Saavedra et al, ; De santos et al, ) could be resulting in a commercial, toxicologically safe green pesticide for public health vector control to replace the currently used insecticides. Our study has identified a potential binary terpene combination against larvae of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Elucidation of mode of action of EOs is important for insect control because it may give useful information on the most appropriate formulation, delivery means and resistance management (Sim et al, ). Future studies emphasizing on determining the mechanism of action, rational design, structure–activity studies, formulation and field trials of the terpenes and EOs as presently going on (Alencar Filho et al, ; Saavedra et al, ; Saavedra et al, ; De santos et al, ) could be resulting in a commercial, toxicologically safe green pesticide for public health vector control to replace the currently used insecticides. Our study has identified a potential binary terpene combination against larvae of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Saavedra et al also found that VP-2 was an important variable responsible for increasing the larvicidal activity of plantderived compounds. 64 Xlog P is a measure of hydrophobicity/ lipophilicity, thereby positively correlated with the toxicity. As depicted in Fig.…”
Section: Qstr Models For Four Aquatic and Terrestrial Speciesmentioning
confidence: 99%
“…M. Javidfar and S. Ahmad have improved QSAR models for 62 larvicidal phytocompounds against Aedes Aegypti [22]. Laura M. Saavedra et al, have analysed by QSAR the larvicidal activity against Aedes aegypti (Diptera: Culicidae) from 60 plant-derived compounds using the RM variable subset selection technique based on MLR exploring 18 326 molecular descriptors [19]. This method attempts to correlate chemical or biological activities with a great number of molecular descriptors, which are real numbers calculated from molecular structures using various approaches and appropriate software [23,25].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, larvicides have been commonly used to eradicate the populations of Culex pipiens for many years [16], so the ideal method for controlling mosquito populations infestation is by preventing mosquitoes at the breeding sites in the aquatic larval stage compared to the adult one [17,18]. However, the development of plant-based larvicides is limited by the considerable time and huge budget to perform biological and clinical trials [19]. For this reason, several approaches have been employed to nd new, quick, and costless methods of research of new bioactive compounds against mosquitoes, which consist in predicting the properties and activities of molecules [20].…”
Section: Introductionmentioning
confidence: 99%